A case of neuronal vacuolation and spinocerebellar degeneration in a juvenile rottweiler. Issue 2 (21st December 2016) - Cowan, Allison Carley; Slanina, Meghan; Choi, April Eun Ju
Abstract : A four‐month old female Rottweiler was presented for a ten‐week history of progressive dyspnoea, spinocerebellar ataxia and tetraparesis that had been unresponsive to empirical treatment. Neurological examination revealed obtundation, an ambulatory tetraparesis (worse in the hindlimbs) with spinocerebellar ataxia, head titubations, miotic pupils, positional vertical nystagmus, an intermittent ventrolateral strabismus and delayed postural reactions in all four limbs. General physical examination revealed inspiratory stridor. Signs were consistent with multifocal neurological disease with involvement of the brainstem, cerebellum, spinal cord and peripheral nerves. Further diagnostics included an MRI, cerebrospinal fluid analysis, and blood work, which were all unremarkable. The multifocal neurological findings in combination with normal ancillary tests in a young rottweiler were suggestive of a degenerative disease, with the top differential being neuronal vacuolation and spinocerebellar degeneration (NVSCD). Due to the grave prognosis and rapid progression of clinical signs, euthanasia was elected. A complete postmortem examination was performed, which revealed multifocal intracytoplasmic neuronal vacuolisation with axonal degeneration throughout the CNS; severe, generalised bilateral myocyte atrophy and degeneration of the cricoarytenoideus dorsalis (CAD) muscles; and moderate, multifocal, bilateral demyelination of the laryngeal nerves. The histological lesions were pathognomonic for NVSCD, thereby confirming the diagnosis.